Human capital and other stories - Dludlu, John (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2018)
My collection of short stories is set mostly in Gauteng and revolves around mainly the lives of the urban, black elite almost three decades after the first non" racial elections in South Africa. It captures emerging trends and fault lines and enquires into whether South Africa can continue on a different path from that of the rest of the continent. Themes covered in the collection, which still espouses idealism, include the acquisition of power, status and money, the use and abuse of these, as well as the psychosocial effects of money on this group. My writing is inspired by the courageous, inventive and introspective writings of the Drum generation of writers William Bloke Modisane, Nat Nakasa and Can Themba, as well as the use of language and the experimental form of writing as embodied in the work of Lidia Yuknavitch to deal with similarly pressing social issues of the day.
Keywords: Short stories, South African (English) -- 21st century; South African fiction (English) -- 21st century